Immunotherapy and immunochemotherapy in combating visceral leishmaniasis - Yadagiri, Ganesh; Singh, Aakriti; Arora, Kanika; Mudavath, Shyam Lal (Frontiers in Medicine, 2023)
Visceral leishmaniasis (VL), a vector-borne disease, is caused by an obligate intramacrophage, kinetoplastid protozoan parasite of the genus Leishmania. Globally, VL is construed of diversity and complexity concerned with high fatality in tropics, subtropics, and Mediterranean regions with ~50,000–90,000 new cases annually. Factors such as the unavailability of licensed vaccine(s), insubstantial measures to control vectors, and unrestrained surge of drug-resistant parasites and HIV-VL co-infections lead to difficulty in VL treatment and control. Furthermore, VL treatment, which encompasses several problems including limited efficacy, emanation of drug-resistant parasites, exorbitant therapy, and exigency of hospitalization until the completion of treatment, further exacerbates disease severity. Therefore, there is an urgent need for the development of safe and efficacious therapies to control and eliminate this devastating disease. In such a scenario, biotherapy/immunotherapy against VL can become an alternative strategy with limited side effects and no or nominal chance of drug resistance. An extensive understanding of pathogenesis and immunological events that ensue during VL infection is vital for the development of immunotherapeutic strategies against VL. Immunotherapy alone or in combination with standard anti-leishmanial chemotherapeutic agents (immunochemotherapy) has shown better therapeutic outcomes in preclinical studies. This review extensively addresses VL treatment with an emphasis on immunotherapy or immunochemotherapeutic strategies to improve therapeutic outcomes as an alternative to conventional chemotherapy.